Geriatric dentistry curriculum in six continents - Xavier, Irina; Ettinger, Ronald L.; Proença, Luís; Botelho, João; Machado, Vanessa; Rua, João; Delgado, Ana Sintra; Mendes, José João (MDPI, 2020)
The purpose of this study was to examine the presence of geriatric dentistry (GD) in the curricula of worldwide dental schools, and to identify and compare their curriculum content. Eighty-three dental schools (16.4% response rate), from 24 countries, in six continents, completed a 25-item online questionnaire, to assess their GD curriculum, and were included in the study. GD was a mandatory course in 56 dental schools (67.5%), an independent subject in 14 schools (16.9%), and was taught as a series of lectures in 31 schools (37.4%). Clinically, 56 dental schools (67.5%) had some form of mandatory education in GD. The type of school, location and method of presentation were not associated with greater interest in expanding their curriculum in GD (p = 0.256, p = 0.276, and p = 0.919, respectively, using the Chi-square test). We found GD is a curriculum requirement in most of the surveyed dental schools and is becoming more common among dental school curricula. This survey is the first study to present data from dental schools from all continents, using a web-based survey which is a resourceful, less-expensive tool to gather data.
Keywords: geriatric dentistry; curriculum development; dental care for aged